Analisis Keterbacaan Cerita Rakyat Bangka Belitung Untuk Pembelajaran Siswa Kelas IV SD Negeri 4 Merawang - Nisa, Anisa; Maulina Hendrik; Sasih Karnita Arafatun (JBES (Journal Basic Education Skills), 2024)
This research was motivated by teachers who had never measured readability in books so that the eligibility of books used in class IV SD Negeri 4 Merawang was unknown. The objectives of this study were: 1.) To find out the feasibility of the storybook Bujang Katak and Because of Fighting for Kelekak based on the readability of the Fry Chart 2.) To find out the feasibility of the storybook Bujang Katak and Because of Fighting for Kelekak based on the readability of the Cloze Test. This type of research uses mixed methods. The population used was fourth grade students at SD Negeri 4 Merawang. The sampling technique in this study was saturated sampling. The sample in this study were 25 grade IV students at SD Negeri 4 Merawang. Data collection techniques using reading and writing techniques and tests. The data analysis technique used in this study on qualitative data, namely data reduction (data reduction), data display (presentation of data) and conclusion drawing/veryfyng (drawing conclusions/verification) and on quantitative data is descriptive statistical data analysis. Based on the results of the readability analysis of Bujang Katak's book using the Fry Chart the book is suitable for grades 3, 4 and 5. The book Due to Fighting for Kelekak uses the Fry Chart the book is suitable for grades 4, 5 and 6. Based on the Cloze Test the Bujang Katak book is included in the independent category means that students easily understand reading. In the book Because of Fighting for Kelekak based on the Cloze Test, the book is included in the instructional category, meaning that students understand enough to read. Based on the results of the Fry Chart qualitative data and the Cloze Test quantitative data, the book Bujang Frog and Because of Fighting for Kelekak is suitable for use in class IV SD Negeri 4 Merawang learning